2010
DOI: 10.1089/cap.2009.0072
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose Olanzapine Monotherapy in Girls with Anorexia Nervosa, Restricting Subtype: Focus on Hyperactivity

Abstract: Low-dose olanzapine monotherapy may be useful as adjunctive treatment of youths with ANr. It is suggested that efficacy may be mediated by a decrease of hyperactivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 27 publications
2
35
0
Order By: Relevance
“…Recent findings suggest that drugs targeting both 5-HT and DA receptors may be effective in treating AN. Several open label studies have reported that the atypical antipsychotic olanzapine (OLZ) increases body weight, and reduces hyperactivity and anxiety about eating and body shape (Barbarich et al, 2004;Dennis et al, 2006;Leggero et al, 2010). Furthermore, two preliminary RCTs recently showed that OLZ significantly reduces obsessions about weight while increasing the rate of weight gain (Bissada et al, 2008), and reduces anorexic ruminations (Mondraty et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Recent findings suggest that drugs targeting both 5-HT and DA receptors may be effective in treating AN. Several open label studies have reported that the atypical antipsychotic olanzapine (OLZ) increases body weight, and reduces hyperactivity and anxiety about eating and body shape (Barbarich et al, 2004;Dennis et al, 2006;Leggero et al, 2010). Furthermore, two preliminary RCTs recently showed that OLZ significantly reduces obsessions about weight while increasing the rate of weight gain (Bissada et al, 2008), and reduces anorexic ruminations (Mondraty et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…It should be always assessed and taken into account, mainly with outpatients. Moreover, an open label trial demonstrated a role for olanzapine in reducing hyperactivity in AN adolescents, mediating weight recovery (Leggero et al 2010). Third, according to the CGAS, all our patients had a high level of functional impairment, with relevant limitations in several areas of functioning.…”
Section: Discussion and Hypothesismentioning
confidence: 72%
“…One small case series of hospitalized adolescents with AN noted increases in rate of weight gain and a reduction in agitation and anxiety, particularly at meal times [73], while another small case series found that preoccupation with body image and anxiety relating to weight decreased but that there was no difference in rate of weight gain before versus after administration of the drug [74]. A small study of adolescents treated with olanzapine for 6 months showed significant increases in BMI after one month of treatment, with continued weight gain throughout the study and improvements in eating attitudes, global functioning scores, anxiety, hyperactivity, and depression [75]. Although the results of these studies are encouraging, none of them were RCTs; the first doubleblinded RCT of olanzapine in female adolescents has been suspended due to difficulties in recruitment [76].…”
Section: Psychiatric Complications and Treatmentsmentioning
confidence: 99%